Dipeptidyl-Peptidase IV inhibitors and glycemic control in type 2 Diabetes Mellitus - Sapkota, Lokendra Bahadur; Thapa, Sangita (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Type 2 diabetes mellitus (T2DM) is a progressive disease, characterized by insulin resistance, impaired glucose-induced insulin secretion, inappropriately elevated glucagon concentrations, and hyperglycemia. Many patients cannot obtain satisfactory glycemic control with current therapies. New and more effective agents, targeted not only at treatment, but also at prevention of the disease, its progression, and its associated complications, are, therefore, required. The dipeptidyl peptidase-4 (DPP-4) inhibitors are a newer class of oral drugs for the treatment of T2DM. They inhibit the breakdown of glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) thereby increasing the incretin effect in patients with T2DM. In clinical practice they are associated with significant reductions in HbA1c, no weight gain and a low risk of hypoglycemia. Since incretin response is markedly diminished in Asian populations, these agents can be used to achieve satisfactory glycemic control in Nepalese T2DM patients. JCMS Nepal. 2016;12(1):28-32.